Near-infrared fluorescent probe with a super large Stokes shift for tracking CO in living systems based on a novel coumarin-dicyanoisophorone hybrid. (November 2019) - Deng, Yingzhen; Hong, Jiaxin; Zhou, Enbo; Feng, Guoqiang
Abstract: A new near-infrared (NIR) fluorescent turn-on probe (CDCI-CO ) based on a novel coumarin-dicyanoisophorone hybrid fluorophore for detection of CO both in vitro and in vivo was reported. By applying Tsuji-Trost reaction to remove the allylcarbonate group, this probe exhibits excellent capability of detecting CO in aqueous solution with rapid response, high selectivity and sensitivity, distinct NIR fluorescent turn-on signal changes at 710 nm, and a remarkable large Stokes shift of 222 nm. The detection limit of this probe for CO was determined to be as low as 33 nM. Moreover, bioimaging of CO in living cells and zebrafish with this probe was also successfully applied, indicating this probe can be used as a promising new tool for studying CO in living systems. Graphical abstract: Image 1 Highlights: A new NIR fluorescent turn-on probe with a remarkable large Stokes shift for detection of CO was reported. This probe is based on a novel coumarin-dicyanoisophorone hybrid fluorophore. This probe shows rapid response, high selectivity and sensitivity for CO. Imaging CO in living cells and zebrafish with this probe was successfully applied.